Optimalisasi Pengelolaan Konten Digital Melalui Tiktok Untuk Meningkatkan Branding Layanan Penyewaan Kantor Di Revio Space Surabaya - Jihan Novita Anggreani; Vian Ahmad Saputra (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2025)
The use of TikTok as a digital marketing medium is an effective way to increase brand awareness for services. This community service activity was carried out to help Revio Space Surabaya improve its TikTok content management in order to strengthen the image of its office rental services. Previous partners faced several obstacles, such as immature content concepts, irregular posting schedules, and limited video quality. Through mentoring and training, the partner was equipped with video content creation skills, content calendar planning, and the implementation of digital marketing strategies tailored to TikTok's characteristics. The results of the activity showed an improvement in the partner's ability to produce more creative and planned content, as well as increased audience interaction and reach. This more optimal TikTok content management has resulted in increased visibility and strengthened branding for the office rental service at Revio Space Surabaya.